The effect of conditioning agents on the corrosive properties of molten urea - Nichols, D. E.; Nguyen, D. T.; Norton, M. M.; Parker, B. R.; Daniels, L. E. (National Fertilizer and Environmental Research Center, Muscle Shoals, AL (United States), 1991)
From the process case histories of the failure of several heat exchanger tube bundles, it was revealed that molten urea containing lignosulfonate as a granulation conditioning-hardening agent (Urea LS[trademark]) is corrosive to Types 304 and 316 stainless steel. The results of field and laboratory immersion corrosion tests indicated that the corrosivity of molten urea is strongly dependent on the process temperature rather than the conditioner composition. At temperatures below 295F, molten Urea LS[trademark] is not aggressive to these stainless steels. However, at temperatures above 300F, the corrosion of these stainless steels is extremely severe. The corrosion rate of Types 304, 304L, 316, and 316L is as high as hundreds of mils per year. The corrosion mechanism tends to be more general than localized. The results of the laboratory corrosion test also revealed that among alloying elements, copper is detrimental to corrosion resistance of stainless steel exposed to molten Urea LS[trademark], chromium is the most beneficial, and nickel has only a minor effect. Thus, copper-free and chromium stainless steels have superior corrosion resistance to the molten Urea LS[trademark] at a wide range of temperatures up to 345F.